Prevalence of Elderly with Oral Complaints Accompanied by Symptoms of Osteoporosis in Jakarta, Indonesia - Palupi, Anggraeny Putri Sekar; Adisa, Aurellia Sophie (Dentistry Faculty, 2025)
Background: Aging is a natural physiological process characterized by a decline in physical, cognitive, and psychomotor functions. These changes can lead to a weakened immune system, making the elderly more vulnerable to various diseases, including osteoporosis, a degenerative condition commonly associated with aging and influenced by multiple factors. Additionally, aging affects oral function, leading to difficulties with mastication and a reduction in nutritional intake. Oral and dental health play a crucial role in maintaining overall health, and inadequate oral care can harm systemic health. Objective: This study aimed to determine the prevalence of elderly individuals with symptoms of osteoporosis and oral health complaints in Central Jakarta. Method: A cross-sectional study was conducted using a structured questionnaire administered to 35 elderly respondents. The collected data were statistically analyzed and presented in the form of a frequency distribution table. Results: The findings revealed that 15% of the respondents exhibited symptoms of osteoporosis. Additionally, 13% of the elderly experienced oral health complaints that coincided with the symptoms of osteoporosis. Conclusion: The study highlights a notable prevalence of osteoporosis symptoms and associated oral health complaints among the elderly in Central Jakarta. These findings underscore the importance of developing integrated health strategies that address both systemic and oral health needs in the elderly population.